WINNING THE TOURISM BUSINESS COMPETITION THROUGH INSTAGRAM ELECTRONIC WORD OF MOUTH AND IMAGE TO INCREASE TOURIST DECISION TO VISIT - Moh. Erfan Arif; Nafisah Devina Sari (Journal of the Community Development in Asia (JCDA), 2022)
The tourism industry today offers increasingly competitive products to retain customers and acquire consumers. This increasingly fierce competition is a consequence of the many players in this industry, so they have to make various efforts. This study aims to examine the effect of electronic word of mouth on destination image, electronic word of mouth on visiting intentions, electronic word of mouth on visiting decisions, destination image on visiting intentions, destination image on visiting decisions, visiting intentions on visiting decisions, electronic word of mouth on the decision to visit through the intention to visit, and the image of the destination on the decision to visit through the intention to visit Dira Park Jember. Samples were taken using a non-probability sampling technique and a purposive sampling method as many as 135 respondents with a minimum age of 18 years, had visited tourist objects, and had accessed tourist attraction information via Instagram. Data analysis used Partial Least Square (PLS) and assisted by SmartPLS 3.0 software. Based on the results of testing the eight hypotheses, it can be concluded that all hypotheses are accepted and have a significant effect. These results confirm the importance of tourism businesses to pay attention to these variables in the face of competition. Keywords: electronic word of mouth, image, intention to visit, decision to visit